KETERWAKILAN PEREMPUAN DALAM KEANGGOTAAN BADAN PERMUSYAWARATAN DESA: Studi Desa Tabbinjai Kecamatan Tombolo Pao Kabupaten Gowa - Muhliza, Nurul; Risal, M. Chaerul; Umar, Kusnadi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
Women's representation in the Badan Permusyawaratan Desa is mandated by the Village Law to encourage women's involvement in policy formulation at the village level. This study aims to analyze women's representation in the Badan Permusyawaratan Desa in Tabbinjai Village, Tombolo Pao District, Gowa Regency in the perspective of Islamic law. This research is a qualitative field research with a legislative and theological approach to syar'i. Data is sourced from primary and secondary data obtained through observation, interviews, and literature studies. Women's representation in the structure of the Badan Permusyawaratan Desa in Tabbinjai Village has fulfilled the provisions of laws and regulations, even though the quota does not reach 30%. The lack of interest and representation of women is influenced by various factors, such as lack of socialization about the role and function of the Badan Permusyawaratan Desa, an election system that seems closed, education level and the choice to focus on other professions. The involvement of women in the public sphere caused dissent among scholars, some expressly forbidding on the basis of hadith narrated by Abu Abkrah. Other scholars, however, argue that the hadith does not apply in general, but only applies to the Persian empire. Because historically, there are examples of women's leadership, both those described in the Qur'an and those that occurred during the time of the Holy Prophetsa and his companions.